Design of IoT-Based Fire Monitoring Using Flame and Smoke Sensors (Dlimas Village) - Mukhamad Iqbal Khusni; Iman Saufik Suasana; Dendy Kurniawan (Jurnal Ilmiah Sistem Informasi, 2026)
Design and Development of Fire Monitoring System Based on Internet of Things Using Flame Sensor and Smoke Sensor (Case Study at Balai Desa Dlimas). Fire is a disaster that can cause significant losses in both material and human life. Early fire detection is crucial to minimize the potential impact. Balai Desa Dlimas, located in Banyuputih District, Batang Regency, currently lacks an adequate fire detection and monitoring system. Therefore, this study aims to design and implement a fire monitoring system based on the Internet of Things (IoT) using an ESP32 microcontroller, a flame sensor, an MQ-2 smoke sensor, and a DHT22 temperature sensor. The research method used is Research and Development (R&D) with a prototyping model. The system is designed to detect the presence of fire, smoke, and room temperature in real time. Data from the sensors is processed by the ESP32 and sent to the Blynk application to notify users. Warning outputs are also provided through a buzzer and LED lights as on-site alerts. The test results show that the system can detect fire, smoke, and temperature increases with high accuracy. Users can receive real-time notifications via the Blynk application within less than 3 seconds of fire detection. This system is expected to help Balai Desa Dlimas minimize fire risk and can be further developed for implementation across various public facilities.